A ZnO/rice husk-based hollow carbonaceous nanosphere composite as an anode for high-performance lithium-ion batteries. Issue 58 (25th September 2018) - Li, Yi; Gao, Yan; Qi, Hui; Yu, Kaifeng; Liang, Ce
Abstract : A new lithium-ion battery anode material was fabricated that had nanorod-like ZnO distributed on the surface of a rice husk-derived carbon skeleton. Abstract : ZnO is considered as a substitute for the next generation of lithium ion battery anode materials because of its high volumetric energy density and abundant resources. In this work, we fabricate a new material that has nanorod-like ZnO distributed in a disorderly fashion on the surface of a rice husk-derived carbon skeleton. Rice husk as a carbon source is suitable for easing the pressure on the environment and improving the utilization of agricultural residues. Its unique interconnected hollow nanosphere structured skeleton provides better support for ZnO loading and electron transport. The ZnO/rice husk-based carbonaceous nanosphere composite samples were characterised by XRD, Raman, SEM and TEM. When used as an anode for lithium-ion batteries, the material exhibited promising Li storage properties and a high specific charge capacity of 920 mA h g −1 at 0.2C after 100 cycles.